Transcriptional Analysis of Nuclear-Encoded Mitochondrial Genes in Eight Neurodegenerative Disorders: The Analysis of Seven Diseases in Reference to Friedreich’s Ataxia - Elsadany, Muhammad; Elghaish, Reem A.; Khalil, Aya S.; Ahmed, Alaa S.; Mansour, Rana H.; Badr, Eman; Elserafy, Menattallah (Frontiers in Genetics, 2021)
Neurodegenerative diseases (NDDs) are challenging to understand, diagnose and treat. Revealing the genomic and transcriptomic changes in NDDs contributes greatly to the understanding of the diseases, their causes and development. Moreover, it enables more precise genetic diagnosis and novel drug targets identification that could potentially treat the diseases or at least ease the symptoms. In this study, we analyzed the transcriptional changes of nuclear-encoded mitochondrial (NEM) genes in eight NDDs. Friedreich’s ataxia (FRDA) is an NDD that cannot be treated effectively, therefore we focused first on FRDA and compared the outcome with the other seven NDDs including Alzheimer’s disease (AD), Amyotrophic lateral sclerosis (ALS), Creutzfeldt–Jakob disease (CJD), Frontotemporal Dementia (FTD), Huntington’s disease (HD), Multiple sclerosis (MS) and Parkinson’s disease (PD). First, weighted correlation network analysis (WGCNA) was performed on an FRDA RNA-Seq dataset, focusing only on NEMs. We then carried out differential gene expression analysis (DEA) and pathway enrichment analysis to pin-point DEGs that are potentially associated with one or more of the analyzed NDDs. Our findings propose a strong link between NEM genes and NDDs and suggest that our identified candidate genes can be potentially used as diagnostic markers and therapeutic targets.